Evaluating Curriculum at Madrasah Aliyah: Applying the Context, Input, Process, Product (CIPP) Model - Muhlil Musolin; Fauzi Fauzi; Hizbul Muflihin (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research aims to evaluate the implementation of the An-Nawawi Sarwodadi Curriculum using the CIPP (Context, Input, Process, Product) model. A qualitative research approach was employed, conducted at Madrasah Aliyah An-Nawawi Sarwodadi in Wonosobo from September to October 2023. Primary data were collected through interviews with school principals, heads of curriculum departments, and teachers, while secondary data included curriculum guidance documents and archives. Data verification was achieved through extended observations, source triangulation, and technical triangulation. Data analysis followed the steps of data collection, data reduction, data display, and drawing conclusions. The results indicate that the context evaluation shows a supportive environment and a good understanding of the curriculum by teachers. Input evaluation revealed that while documents and manuals for teachers and students are available, they remain incomplete. Human resource qualifications and the standardization of facilities and infrastructure are satisfactorily met. Process evaluation demonstrated that teachers effectively implemented the curriculum, including organizing learning administration, conducting classroom activities (initial, core, and final), and performing assessment activities such as daily tests and mid-semester and final semester exams. Product evaluation showed good student learning outcomes, and most teachers efficiently input grades. Overall, the curriculum implementation is considered good. However, to further improve the quality of education, it is necessary to enhance the completeness of facilities and infrastructure, increase student participation in learning, and boost teacher competency through training and workshops.